Pengangkatan Anggota Tentara Nasional Indonesia dan Kepolisian Negara Republik Indonesia Aktif Menjadi Penjabat Kepala Daerah - Putra, Egip Satria Eka; Fahmi, Khairul; Yuslim, Yuslim; Khairani, Khairani; Andora, Hengki (Universitas Ekasakti, 2023)
The Assignment of members of the Indonesian National Army and the National Police of the Republic of Indonesia active as acting regional heads by the Minister of Home Affairs reaped polemics. Law Number 10 of 2016 concerning Regional Elections even though it has clearly regulated the filling of vacancies in the positions of governor, regent and mayor, where acting (Pj.) are appointed from the position of intermediate leaders for the Acting Governor and primary leaders for the Acting Regent and Mayor. However, the Minister of Home Affairs issued Minister of Home Affairs Regulation Number 4 of 2023 concerning Acting Governors, Regents and Mayors as a reference to fill the position of Acting Regional Head. Article 3 paragraph (b) of Permendagri Number 4 of 2023, contains norms stating that the acting regional head is from an ASN official or an official in a certain ASN position who occupies JPT Madya within the Central Government or within the Regional Government for candidates for Pj. Governor and occupies JPT Pratama within the Central Government or within the Regional Government for candidates for Pj. Regent and Pj. Mayor. Therefore, there is an addition of position criteria and an expansion of meaning in Permendagri Number 4 of 2023 which then becomes a gap and opportunity for the Minister of Home Affairs to appoint active TNI and Polri members to become Acting (Pj.). The formulation of the problem in this study is: (1) How is the validity of the appointment of members of the Indonesian National Army and members of the Negatra Police of the Republic of Indonesia active as Acting Regional Heads? (2) What are the criteria for the ideal official who can be appointed as Acting Regional Head? (3) What is the ideal mechanism for appointing and appointing acting regional heads to fill regional head vacancies ahead of the 2024 simultaneous regional elections? This research is a normative legal research or literature, with the research specifications used are analytical descriptive research. The results of this study are: (1) The appointment of members of the Indonesian National Army and active members of the Indonesian National Police to become Acting Regional Heads is not legally positive Indonesia at this time. (2) The position of the official who should be appointed as Pj. Regional Head shall be JPT Madya within the Central Government or within the Regional Government. (3) the ideal mechanism for the appointment and appointment of acting regional heads is to involve the people through the Senators so that the appointed PJ. still has legitimacy from the people.